An experimental study of the impact of cool roof on solar PV electricity generations on building rooftops in Sharjah, UAE. (5th February 2019) - Altan, Hasim; Alshikh, Zahraa; Belpoliti, Vittorino; Kim, Young Ki; Said, Zafar; Al-chaderchi, Monadhil
Abstract: Cool roof is the technique that delivers higher solar reflectance and higher thermal emittance than standard roofing products. Its fastest developing applications in the built environment comes with various benefits, such as reducing the urban heat island effect by decreasing surface temperatures, which reduces the flow of heat into the atmosphere, and offsetting warming caused by greenhouse gases. In this study, a Cool Coating Paint has been experimented while the impact was measured in terms of an integration with the Solar PV technology. This research investigated cool roof applications on building's rooftop together with PV panels for the Middle East climatic conditions, and its impact on the electricity generation. The preliminary findings of the experimental study indicated that there is a likely impact of 5–10% improvement of electricity generation with the cool roof applications.